Design of a transfer robot for the assistance of elderly and disabled. (16th February 2021) - Wu, Ruikai; Wang, Jingchuan; Chen, Weidong; Wang, Pu
Abstract : The decline in muscle strength of the lower limbs because of ageing and diseases is the main reason why elderly and disabled have difficulty in standing and walking. In this paper, a transfer robot is designed to assist the elderly and disabled in standing and moving. The robot uses the traction assist method to lift the user, which can reduce the user's lower limb muscle force during the standing process. The structure of the robot was optimized through a biomechanical analysis software to minimize the user's lower limb muscle force during the lifting process. The robot has three different control modes, including the autonomous transferring mode. One healthy person and three stroke patients were invited in the experiment to evaluate the robot. Electromyographic signals of subjects' lower limbs muscles were recorded to analyse subjects' muscle force during the standing process. The results showed that the assisted standing by the transfer robot reduced the muscle force of the user's lower limb. GRAPHICAL ABSTRACT: UF0001